Meningkatkan Minat Belajar dan Kepercayaan Diri Remaja Panti Asuhan Menggunakan Media Youtube - Azizzi Munawwar Simbolon; Berlianti (Yayasan Literasi Sains Indonesia, 2022)
Confidence and interest in learning are two important aspects that must be possessed by children who are entering their teens. Teenagers should have good self-confidence and interest in learning, if they feel less confident and their interest in learning decreases, this will have fatal consequences when they reach adulthood. They will become individuals who tend to close themselves and find it difficult to be active in their social environment. One of the teenagers at the Ora Et Labora Nusantara Orphanage in Medan also experienced the same thing, he needed professional help to help him regain his confidence and interest in learning. The assistance process provided was also carried out in the PKL 1 mini project activity, using the casework method through the general intervention stage consisting of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation and Termination. The focus of solving client problems in the intervention process this time is honing the interests and talents of clients through watching via Youtube media and accompanied by joint discussions as a strategy designed to increase the client's confidence and interest in learning. The objectives of this program are stated to have been achieved, as evidenced by the return of self-confidence and increased client interest in learning.